Synthesis and Crystal Structure of [(phen)3Co]2?Ni(SCN)6 - Bi, Jian-Hong; Bi, Wen-Tao; Huang, Zi-Xian; Hu, Nai-Liang (Asian Journal of Chemistry, 2010)
A novel compound [(phen)3Co]2.Ni(SCN)6 where phen = 1,10-phenanthroline, was synthesized and characterized by IR spectra, elemental analysis and single-crystal X-ray. The crystal is monoclinic, space group P2(1)/n with unit cell parameters: a = 10.2295(19)Å, b = 19.413(4)Å, c = 18.951(4)Å, α = 90º, β = 95.157(3)º, γ = 90º, V = 3748.3 (12)Å3, Z = 2, Mr = 1722.43, Dc = 1.526 Mg/cm3, μ = 0.970 mm-1, F(000) = 1756, T = 293(2) K, R = 0.0459, wR = 0.1239 for 28699 reflections with I > 2s(I).